THE ROLE OF EDUCATION AND TRAINING IN FOSTERING WORKPLACE DIVERSITY AND INCLUSION IN DIGITALLY ORIENTED ORGANIZATIONS - Jelena LukicŃikolic\'; Pero Labus (Agora International Journal of Economical Sciences (AIJES), 2024)
The aim of this paper is to emphasize the role and importance of employee education and training in digitally oriented organizations so that they can recognize, comprehend, and accept diversity and inclusion in the workplace. Digitally oriented organizations have the advantage of remote work and flexible working hours, which allow for the inclusion of individuals who may not meet the requirements of traditional work environments, involving physical presence for eight hours a day. Conducted desk research shows that education and training on diversity and inclusion in digitally oriented organizations have an important role in raising awareness, promoting understanding, and supporting positive behaviors within all employees. The main advantages of workplace diversity and inclusion are a more diversified and high-quality pool of candidates, a better organizational reputation among employees, increased innovation, and higher profitability. To fully realize these benefits, it is essential that all employees wholeheartedly embrace and foster diversity and inclusion. This paper's theoretical implications include a systematic review and analysis of existing literature on the topic, while practical implication is in providing key recommendations to leaders and managers for achieving high levels of diversity and inclusion in the workplace through education and training.
Keywords: 330